Using graphics processors to facilitate explicit digital electrochemical simulation: Theory of elliptical disc electrodes - Cutress, I; Compton, R (2010)
The use of graphics processors under the heading GPGPU (general-purpose computation on GPUs (graphics processing units)) promises a computational advance which may greatly facilitate the use of explicit digital simulation for non-trivial problems. This paper illustrates the use of GPGPU for the simulation of mass transport processes at elliptically shaped electrodes and for deformed microelectrodes. Under explicit algorithm conditions, this paper finds a mid-range commercial GPU affords a fivefold increase in simulation speed, at an eighth of the cost, over a 16-thread high-range professional workstation PC. This work shows also the difficulties of confirming the regularity of size and shape, from purely voltammetric studies, of microdisc electrodes. © 2010 Elsevier B.V. All rights reserved.